2017
DOI: 10.1016/j.jpba.2017.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Development of an enzyme-linked immunosorbent assay for detection of CDCP1 shed from the cell surface and present in colorectal cancer serum specimens

Abstract: Development of an enzyme-linked immunosorbent assay for detection of CDCP1 shed from the cell surface and present in colorectal cancer serum specimens, Journal of Pharmaceutical and Biomedical Analysis http://dx.doi.org/10. 1016/j.jpba.2017.02.047 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…The intracellular domain of CDCP1 has multiple tyrosine residues that can be phosphorylated by Src kinase family, and the activated CDCP1 promotes migration and invasion of malignant tumor cells. 26 , 27 , 28 For tumor cells, inhibition of CDCP1 activity or reduction of CDCP1 expression level can limit anchorage-independent survival which plays a vital role in tumor metastasis. 29 , 30 Based on the experiments above, we hypothesized that CDCP1 protein clusters may be functional domains that promote proliferation and metastasis of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The intracellular domain of CDCP1 has multiple tyrosine residues that can be phosphorylated by Src kinase family, and the activated CDCP1 promotes migration and invasion of malignant tumor cells. 26 , 27 , 28 For tumor cells, inhibition of CDCP1 activity or reduction of CDCP1 expression level can limit anchorage-independent survival which plays a vital role in tumor metastasis. 29 , 30 Based on the experiments above, we hypothesized that CDCP1 protein clusters may be functional domains that promote proliferation and metastasis of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…CDCP1 is a 135 kDa cell surface protein that can undergo proteolytic cleavage in vitro and in vivo by serine proteases including matriptase and proteases of the plasminogen activation system. , After proteolysis, CDCP1 is present as a 70 kDa membrane spanning the carboxyl-terminal fragment (CTF) and a 65 kDa amino-terminal fragment (ATF) that binds to the plasma membrane via CDCP1-CTF or full-length CDCP1 or is shed from the cell surface and can be detected in conditioned cell culture media and colorectal cancer patient blood. , Because 10D7 binds to CDCP1-ATF, shedding of this fragment from the cell surface would prevent the antibody binding to CDCP1 to deliver a fluorescent payload such as ICG.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our flow cytometry results suggest that ex vivo evaluation of levels of cell surface CDCP1 in tumor biopsies or circulating malignant cells could also serve to stratify patients for CDCP1-targeted therapies. In addition, because we and others have shown that a region of CDCP1 can be shed from the cell surface and detected in colon cancer patient serum and function as a predictive biomarker of lung cancer onset [11,34,35], the detection of cell-shed CDCP1 may be suitable for selection of cancer patients suitable for CDCP1-targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…These signalling events via CDCP1 are generally accompanied by its phosphorylation at residue tyrosine 734 (Y734) 10 . CDCP1-ATF is detectable in the serum of colorectal cancer patients 11 but appears to remain predominantly on the plasma membrane tethered to CDCP1-FL or CDCP1-CTF 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%